Selection of Feature Driven Development (FDD) Model in Agile Method for Developing Information System of Mosque Management - Sasmitoh Rahmad Riady; Khalis Sofi; Jafar Shadiq; Rita Wahyuni Arifin (Information Technology and Science (ITScience), 2022)
This paper discusses about software development for building a project using the Feature Driven Development (FDD) model contained in the agile method. As in other agile methods, the Feature Driven Development model has additional properties to implement functions and needs in a short iteration. In terms of the characteristics contained in several other agile models almost all of them have similarities so that makes the stakeholder confusion in determining which model will be chosen as a method of software development. This study focuses on the search for a number of suitable project specifications in the selection of Feature Driven Development models for software development. From the research that has been done on several papers there are several aspects of design and construction in software development by emphasizing the quality and high level of features in developing a software using the Feature Driven Development model. In facilitating the results of the Feature Driven Development model, we will provide a case study of Mosque Management Information System which has several features, such as content management, information of prayer time, online reading Qur’an, and Petty Cash Mosque management. This case is implemented by Feature Driven Development model with short iteration, because this project had done in several months